2018
DOI: 10.1002/cam4.1600
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant endocrine therapy with exemestane followed by response‐guided combination therapy with low‐dose cyclophosphamide in postmenopausal patients with estrogen receptor‐positive breast cancer: A multicenter, open‐label, phase II study

Abstract: Patients with estrogen receptor (ER)‐positive breast cancer are less likely to achieve a pathological complete response (pCR) with neoadjuvant chemotherapy. Neoadjuvant endocrine therapy may be more appropriate than neoadjuvant chemotherapy in these hormone‐sensitive patients. Most patients with ER‐positive breast cancer are postmenopausal, and therefore, generally older and less able to tolerate chemotherapy. We aimed to investigate the efficacy and safety of tailored neoadjuvant endocrine and chemoendocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 37 publications
6
41
1
Order By: Relevance
“…The study design, which closely followed the one used in our previously reported study, is shown in Figure . Both are multicenter, open‐label, phase II studies.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study design, which closely followed the one used in our previously reported study, is shown in Figure . Both are multicenter, open‐label, phase II studies.…”
Section: Methodsmentioning
confidence: 99%
“…The eligibility criteria were postmenopausal status; diagnosis of primary invasive ER‐positive, human epidermal growth factor receptor 2 (HER2)–negative, stage I‐IIIA (T1c–T3, N0‐2, M0) breast cancer (confirmed by needle biopsy or histological findings); Ki67 labeling index ≤30%; Eastern Cooperative Oncology Group performance status 0 or 1; indication for partial or total mastectomy; and no previous treatment for cancer. ER‐positive status was confirmed by immunohistochemistry, and HER2‐negative status by either immunohistochemistry or fluorescence in situ hybridization, as described previously . Patients with or without axillary lymph node metastasis were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations